The Impact of Artificial Intelligence and Big Data Technologies on the Profession of Accounting Educators - Inta Budi Setya Nusa; Adi Rachmanto; Mahmad Hasan H. Alhilo (Australasian Accounting, Business and Finance Journal, 2024)
This research investigates the impact of Artificial Intelligence (AI) and Big Data technologies on the accounting profession, explicitly focusing on accountants who serve as educators. The rapid development of AI and Big Data technology has changed teaching approaches and curricula in accounting education.. The research methodology involves surveys and interviews with accounting educators affiliated with the Indonesian Institute of Accountants, specifically within the Educator Accountants Department, from various higher education institutions in Indonesia. Data obtained from these interviews are qualitatively analyzed to identify their perspectives on the impact of AI and Big Data technologies in the context of teaching and accounting practices. The findings reveal that accounting educators widely recognize the importance of integrating AI and Big Data concepts into accounting curricula. This research provides valuable insights for educators to be able to design responsive curricula and equip students with the skills necessary to succeed in an increasingly interconnected and digitally transformed work environment.
Keywords: Artificial Intelligence (AI); Big Data technologies; Accounting profession; Educator accountants; Teaching approaches.